FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG (Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Dana Sagita Devi, 15.05.52.0301; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2019)
The study examines the effect of institutional ownership, dividend policy, company size, profitability, and sales growth on debt policy. The population of this research is all manufacturing companies listed on Indonesia Stock Exchange for year of 2015 to 2017. The sampling method uses purposive sampling with the research period from 2015-2017 producing 149 samples. Method of data analysis of the study is multiple regression analysis. The results showed that institutional ownership does not affect debt policy, dividend policy does not affect debt policy,company size negative affects debt policy, profitability has a negative effect on debt policy, and sales growth has a positive effect on debt policy.